Testing the Assumptions in the Process of Cultural Competence in the Delivery of Healthcare Services Using Empirical Data, Focusing on Cultural Awareness. (May 2023) - Sahamkhadam, Nasrin; Andersson, Anna Karin; Golsäter, Marie; Harder, Maria; Granlund, Mats; Wahlström, Emmie
Introduction: Encounters with children of foreign origin call for school nurses' cultural competence during the health visits. This study aimed to investigate the statistical associations between the cultural constructs described by the Process of Cultural Competence in the Delivery of Healthcare Services (PCCDHS) model and whether school nurses' cultural encounters, cultural knowledge, and cultural skill could statistically predict their cultural awareness. Methodology: Spearman correlation and hierarchical regression analyses were conducted using cross-sectional secondary data from 816 Swedish school nurses. The cultural constructs in the theoretical description of the PCCDHS model guided the selection and sorting of the items on cultural competence. Results: The constructs of cultural knowledge, cultural skill, cultural encounters, and cultural awareness were positively correlated with each other. However, becoming culturally aware was not statistically predicted by included cultural constructs ( R 2 = 13.4, p = .06). Discussion: Despite the interrelations between the investigated cultural constructs of the PCCDHS model, understanding cultural awareness development requires further empirical testing.